Optimizing Performance - Khairul Ibaad Pohan, Muhammad; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
This research aims to examine the influence of leadership style and organizational culture on employee performance in the moderated work climate at the Bank Indonesia Representative Office, North Sumatra Province. Humans need special attention because basically they are able to develop, have reasons, ideas, feelings, desires and hopes. These variables also influence achievement, dedication, loyalty and love of work as well as organizational success. Therefore, human resource management is very necessary to improve employee performance, so that it is beneficial for the company and able to survive in a competitive and dynamic business climate. The results of this research are as follows: Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.446 and ap value of 0.000. Work Climate cannot moderate Leadership Style on Employee Performance with an original sample value of -0.033 and ap value of 0.420. Work Climate is unable to moderate Organizational Culture on Employee Performance with an original sample value of 0.031 and ap value of 0.419. Leadership style has a positive and insignificant effect on employee performance with an original sample of 0.115 and ap value of 0.128. Work Climate has a positive and significant effect on Employee Performance with an original sample value of 0.392 and ap value of 0.000.